Language, Representation and Fetish. Hunger in “The Shawl” by Cynthia Ozick - Sowiński, Bartosz (Respectus Philologicus, 2021)
The Shawl by Cynthia Ozick is an extremely intriguing attempt at writing hunger, loss and the Holocaust. The novella transforms into a meditation on the possibility of depicting traumatic sensations, which easily defy symbolisation. As she casts suspicion on language and literature, and more broadly representation, Ozick adheres to the tradition of Jewish aniconism. However, she does so in an ostentatiously literary manner, verging on the idolatry of fiction. Ozick discards verisimilitude and hyperrealism in the representations of hunger and the Holocaust. In so doing, she suggests that the illusion of immediacy they produce is merely a fetish rather than the literary celebration of the body. Ozick’s ambitions may be more moderate, but they are certainly more honest. She explores the irreconcilable differences between the realms of the sensual and the literary. However, she also seems to say “literature in spite of all” (to misquote Georges Didi-Huberman’s dictum), thereby articulating her affirmation of the linguistic medium and literature despite all their shortcomings and deficiencies.
Keywords: Cynthia Ozick; hunger; language; fetish; representation